Helicobacter pylori outer membrane vesicles and infected cell exosomes: new players in host immune modulation and pathogenesis - Wang, Xiuping; Wang, Jianjun; Mao, Lingxiang; Yao, Yongliang (Frontiers in Immunology, 2024)
Outer membrane vesicles (OMVs) and exosomes are essential mediators of host-pathogen interactions. Elucidating their mechanisms of action offers valuable insights into diagnosing and treating infectious diseases and cancers. However, the specific interactions of Helicobacter pylori (H. pylori) with host cells via OMVs and exosomes in modulating host immune responses have not been thoroughly investigated. This review explores how these vesicles elicit inflammatory and immunosuppressive responses in the host environment, facilitate pathogen invasion of host cells, and enable evasion of host defenses, thereby contributing to the progression of gastric diseases and extra-gastric diseases disseminated through the bloodstream. Furthermore, the review discusses the challenges and future directions for investigating OMVs and exosomes, underscoring their potential as therapeutic targets in H. pylori-associated diseases.